Fenomena Feminisme dalam Novel Cinta Suci Zahrana Karya Habiburrahman El Sirazy - Yeni, Syafrima; Abdurahman, Abdurahman; Nst., M. Ismail (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The purposes of this research is to describe, profeminismÂ  phenomenon that reflected character, contrafeminism phenomenon of the character, the opposition and firmed of feminism in novel Cinta Suci Zahrana that created by Habiburrahman El Shirazy, The implication is to Indonesian learning. The data of the research is profeminism and contrafeminism in novel Cinta Suci Zahrana created by Habiburrahman El Shirazy. The method that used to collect the data is read and takes notes. The technique to collect the data of the research are (1) read and comprehend the phenomenon of feminism (2) signing part of novel that show profeminism phenomenon and contrafeminism in novel by Habiburrahman El Shirazy, Cinta Suci Zahrana; (3) researcher include and collect the data into research format. Researcher invented that profeminism characters are Zahrana, Lina, Hasan, Orangtua Zahrana, Pak Munajat (Zahranasâ€™ father), Nuriyah (Zahranasâ€™ mother), if we looked in, there is prasangka gender that want to treat woman best, but in the other hand, they still caged the woman in the â€œgold cageâ€. And the characters of contrafenimism are Mr. Sukarman, Mr. Didik, and the person who send terror SMS. They think that they can make woman falling in love by money and power. The imlpication in Indonesian learning is to improve reading literature ability in learning Indonesian.